2019
DOI: 10.1515/les-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Translator Education at a Crossroads:the Impact of Automation

Abstract: Automation is affecting all spheres of our daily lives and humans are adapting both to the challenges that it poses and the benefits that it brings. The translation profession has also experienced the impact of new technologies with Language Service Providers adapting to changes (Presas/Cid-Leal/Torres-Hostench 2016; Sakamoto/Rodríguez de Céspedes/Evans/Berthaud 2017). Translation trainers are not oblivious to this phenomenon. There have indeed been efforts to incorporate the teaching of digital translation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In Europe, many translation programmes have already incorporated the teaching of necessary technological competence into their curricula [13]. However, this study found that most current translation learners have not received formal training in MT.…”
Section: Perceived Necessity Of Incorporating Mt Training Into Transl...mentioning
confidence: 71%
See 1 more Smart Citation
“…In Europe, many translation programmes have already incorporated the teaching of necessary technological competence into their curricula [13]. However, this study found that most current translation learners have not received formal training in MT.…”
Section: Perceived Necessity Of Incorporating Mt Training Into Transl...mentioning
confidence: 71%
“…The sustainability issue in the field of translation has been discussed mainly in two strands. Some scholars have examined the sustainability of translation industry and translation profession as a result of technological development [13], whereas some have examined translation as a profession that can make an impact on ecological and environmental systems in the long run [14]. In the context of using machine translation in translation teaching, research mainly follows the first strand, in which sustainability denotes to what extent potential MT use can impact on the sustainability of the translation ecosystem including the translation profession (thus translator education).…”
Section: Introduction 1translation and Technologymentioning
confidence: 99%
“…A similar survey of translation technology adoption (Man et al, 2020) among 441 Chinese students enrolled on a MA Programme in Translation and Interpreting demonstrated a strong, positive correlation between students' knowledge and their use of translation technology. Other authors (Kenny & Doherty, 2014;Rodríguez de Céspedes, 2019) also support the idea of designing and implementing a new translator-oriented MT syllabus, arguing for a holistic approach to the integration of MT into translator training programmes, one that empowers rather than marginalises translators.…”
Section: Introductionmentioning
confidence: 99%
“…Díaz-Millón et al [ 52 ] introduced transcreation in a French-Spanish translation course at the University of Granada, Spain. Facing the threat of automation such as machine translation, Rodríguez De Céspedes [ 53 ] stressed the mastery of language skills that involve creativity although she did not point to transcreation specifically (p.113). Universities in the UK such as the University College London offer a short course, usually online, giving trainees not only an introduction to transcreation but also a chance to practice it on real texts, as presented in Fig 3 [ 54 ].…”
Section: Introductionmentioning
confidence: 99%